2021
DOI: 10.1155/2021/6346703
|View full text |Cite
|
Sign up to set email alerts
|

Study on Major Parasitic Diseases of Adult Honeybees in Three Districts of Kaffa Zone, Southern Ethiopia

Abstract: Background and Methods. Since regular and timely control of all factors that endanger honeybee life and threaten their products is needed for effective apiculture, cross-sectional research was performed in the three districts (Bonga, Chena, and Gimbo) of the Kaffa Zone to assess the prevalence of major honeybee diseases. A total of 384 honeybee samples from 15 operating apiaries were chosen from each kebele based on their ability to provide a bee sample and the apiary farm’s accessibility. From each district, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…However, the association between amoeba prevalence and agro-ecology as well as hive type was not significant (p > 0.05). Although similar results have been reported that amoeba is more common in highland areas than lowland and midland agro-ecologies [13] as well as in traditional hives than modern hives [11], these works did not state whether there was an association between agro-ecologies as well as hive types or not. Moreover, amoeba was more prev-alent in traditional hives than modern hives, which is similar with the previous in North Gondar.…”
Section: Prevalence Of Honeybee Diseases and Pestsmentioning
confidence: 54%
“…However, the association between amoeba prevalence and agro-ecology as well as hive type was not significant (p > 0.05). Although similar results have been reported that amoeba is more common in highland areas than lowland and midland agro-ecologies [13] as well as in traditional hives than modern hives [11], these works did not state whether there was an association between agro-ecologies as well as hive types or not. Moreover, amoeba was more prev-alent in traditional hives than modern hives, which is similar with the previous in North Gondar.…”
Section: Prevalence Of Honeybee Diseases and Pestsmentioning
confidence: 54%
“…It has been reported that the presence of M. mellificae in honeybees correlates with Nosema spp. infections [ 241 , 242 ]. Until now, diagnostics has been carried out by microscopic observation of Malpighian tubes [ 240 ].…”
Section: Description Of Main Bee Pathogens and Molecular Methods For ...mentioning
confidence: 99%
“…It is all the more important to introduce quarantine and establish strict compliance with bans on importing bee packages and queen bees and bumblebees into Europe (certificates of wellbeing!) and trade in wax and bee products, as well as regular monitoring and inspection of bee colonies (Silacci et al, 2018;Huwiler et al, 2020;Hopkins & Keller, 2021;Solomon et al, 2021).…”
Section: Prevention and Control Measuresmentioning
confidence: 99%